Enhancing Early Writing Skills in Slow Learners Through Learning by Doing: A Contextual Classroom Action Research - Hindriyani, Eli; Purwanta, Edi (Papanda Publisher, 2025)
Early writing development is critical for academic success, yet slow learners face significant challenges in acquiring these foundational skills. This study investigated the effectiveness of learning by doing methodology based on contextual learning in enhancing early writing abilities among kindergarten slow learners. A classroom action research design using the Kemmis and McTaggart cyclical model was implemented with one male slow learner (age 7) in Group B at TK Negeri 2 Muara Wahau, Indonesia. The intervention consisted of two cycles incorporating hands-on activities, visual aids, and concrete objects connected to daily life experiences. Data collection employed observation instruments, writing assessments, and interviews. Pre-test and post-test evaluations measured writing competency across six indicators including line tracing, letter formation, syllable construction, and name writing. The participant demonstrated substantial improvement from baseline pre-test (36%) through Cycle I post-test (55%) to final Cycle II post-test (80%), representing a 44% overall improvement. The intervention successfully enabled independent line tracing, vowel and consonant recognition, basic syllable formation, and supported name writing. Observational data revealed enhanced attention span, task persistence, and learning engagement across intervention cycles. The findings support the effectiveness of experiential learning approaches for slow learners, validating theoretical frameworks emphasizing concrete, contextual instruction. However, the intensive individualized instruction required may limit practical scalability in typical classroom settings. The study contributes empirical evidence for learning by doing methodology in special education while highlighting the importance of multisensory, contextually-relevant instruction for students with mild intellectual disabilities.